Basalt fiber ropes and rods: Durability tests for their use in building engineering. (March 2016) - Quagliarini, Enrico; Monni, Francesco; Bondioli, Federica; Lenci, Stefano
Abstract: Basalt is a common material used in constructions since antiquity. Nowadays its fibers (BFs) are going to be used as an alternative to glass, carbon or aramid fibers for strengthening purposes in building engineering. In particular, the use of basalt ropes on historic masonries seems to be a good solution to give them a monolithic behavior. Besides, basalt fibers reinforced polymer (BFRP) rods have emerged as a possible solution to the corrosion problems of steel reinforcement in reinforced concrete for new or damaged structures or to the strengthening of historic masonries by repointing. Anyway, there is till a lack of knowledge about their durability. Thus this paper presents durability tests performed on BF ropes and BFRP rods. The influence of water, acid and alkali aging solutions on the durability and on the mechanical strength of them was verified. In order to increase the durability in alkali environments (i.e.: concrete), a PMMA coating was also applied on the BFRP rods and its effect was assessed too. Results show that alkali environments could seriously affect the durability of BF ropes and BFRP rods, thus a suitable coating should be provided to protect them before their use on such environments. Highlights: BF ropes and BFRP rods have emerged as possible products for building engineering, but in literature there is a lack of knowledge about the durability of these basalt products. Good results have emerged from water and acid environments. Alkali environments could seriously affect the durability of BF ropes and BFRP rods. A PMMA coating was applied on the BFRP rods and a better - but limited - effect of this was found. The mass loss before and after aging cannot be used as a durability parameter.